The idea of ​​death and nothingness in the construction of the dramatic testicle selected models (Journal of the College of Basic Education, 2022)
The basic starting point for this study is the intellectual value of the symbolic significance of the philosophy of nothingnessAnd its impact on the dramatic personality, which was adopted by most of the arts and literature, is a re-evaluation or a reversalBelief in the idea of ​​the futility of life is the focus of the writings of researchers, philosophers and artistsDiversity and multiplicity of other life issues that were sources of interest; I picked up an ideaMany philosophers, artists, and writers dealt with the nihilistic personality in their literary productionsAnd artistic. Here we try to focus in this study on one of the angles of this approachIt is the view of drama and its impact on the idea of ​​death leading to the construction of the nihilistic personality of a bookTheater and references to this idea and its philosophies The idea of ​​existential value, which originated in